Gata3 restrains B cell proliferation and cooperates with p18(INK4c) to repress B cell lymphomagenesis - Liu, Shiqin (Oncotarget, 2016)
GATA3, a lineage specifier, controls lymphoid cell differentiation and its function in T cell commitment and development has been extensively studied. GATA3 promotes T cell specification by repressing B cell potential in pro T cells and decreased GATA3 expression is essential for early B cell commitment. Inherited genetic variation in GATA3 has been associated with lymphoma susceptibility. However, it remains elusive how the loss of function of GATA3 promotes B cell development and induces B cell lymphomas. In this study, we found that haploid loss of Gata3 by heterozygous germline deletion increased B cell populations in the bone marrow (BM) and spleen, and decreased CD4 T cell populations in the thymus, confirming that Gata3 promotes T and suppresses B cell development. We discovered that haploid loss of Gata3 reduced thymocyte proliferation with induction of p18(Ink4c) (p18), an inhibitor of CDK4 and CDK6, but enhanced B cell proliferation in the BM and spleen independent of p18. Loss of p18 partially restored Gata3 deficient thymocyte proliferation, but further stimulated Gata3 deficient B cell proliferation in the BM and spleen. Furthermore, we discovered that haploid loss of Gata3 in p18 deficient mice led to the development of B cell lymphomas that were capable of rapidly regenerating tumors when transplanted into immunocompromised mice. These results indicate that Gata3 deficiency promotes B cell differentiation and proliferation, and cooperates with p18 loss to induce B cell lymphomas. This study, for the first time, reveals that Gata3 is a tumor suppressor specifically in B cell lymphomagenesis.